Addressing Global and National Concerns into Local Actions: Reflecting Customary Institution’s Involvement in Combating Drug Abuses - Wirasila, Anak Agung Ngurah; Takácová, Jana (Udayana Journal of Law and Culture; Vol 3 No 1 (2019): Contemporizing Cultural ElementsDO - 10.24843/UJLC.2019.v03.i01.p02, 2019)
The massive movement of transnational drug-dealers has now been approaching society at the lowest level. This article is aimed at exploring how customary institution in Bali-Indonesia, namely desa pakraman (customary village) is involved in any efforts of combating drug abuse, as a complementary means of the official measures taken by Indonesian agencies that responsible for this matter. It is legal research that inquiries relevant legal documents. Besides, it discovers customary village leaders opinion by using informant interview questionnaires as well as impression obtained from direct observation. This paper discovers that there have been many customary villages modified their customary rule by incorporating the norms on prohibition of the use and sale of narcotics as well as adopted customary sanction to be imposed on those who violate it. This article also suggests that the involvement of customary institution may be used as a lesson learned regarding how the non-state actors, especially a community-based institution, may play a role to support the government in the eradication of drug abuses and crimes.